Feasibility and efficacy of combined pancreatic islet‐lung transplantation in cystic fibrosis‐related diabetes–PIM study: A multicenter phase 1–2 trial. Issue 7 (26th April 2022) - Rakotoarisoa, Luc; Wagner, Clothilde; Munch, Marion; Renaud Picard, Benjamin; Grenet, Dominique; Olland, Anne; Greget, Michel; Enescu, Iulian; Bouilloud, Florence; Bonnette, Pierre; Guth, Axel; Bosco, Domenico; et al.
Abstract : Cystic fibrosis‐related diabetes (CFRD) is a common complication of cystic fibrosis (CF), and restoring metabolic control in these patients may improve their management after lung transplantation. In this multicenter, prospective, phase 1–2 trial, we evaluate the feasibility and metabolic efficacy of combined pancreatic islet‐lung transplantation from a single donor in patients with CFRD, terminal respiratory failure, and poorly controlled diabetes. Islets were infused via the portal vein under local anesthesia, 1 week after lung transplantation. At 1 year, the primary outcome was transplant success as evaluated by a composite score including four parameters (weight, fasting glycemia, HbA1c, and insulin requirements). Ten participants (age: 24 years [17–31], diabetes duration: 8 years [4–12]) received a combined islet‐lung transplant with 2892 IEQ/kg [2293–6185]. Transplant success was achieved in 7 out of 10 participants at 1‐year post transplant. Fasting plasma C‐peptide increased from 0.91 μg/L [0.56–1.29] to 1.15 μg/L [0.77–2.2], HbA1c decreased from 7.8% [6.5–8.3] (62 mmol/mol [48–67]) to 6.7% [5.5–8.0] (50 mmol/mol [37–64]), with 38% decrease in daily insulin doses. No complications related to the islet injection procedure were reported. In this pilot study, combined pancreatic islet‐lung transplantation restored satisfactory metabolic control and pulmonary function in patients with CF, without increasing the morbidity of lung transplantation. Abstract : In a cohort of patients with cystic fibrosis‐related diabetes, this pilot study demonstrates that lung combined with islet transplantation which is less invasive than whole pancreas transplantation restored satisfactory metabolic control and pulmonary function, without increasing morbidity.